2013
DOI: 10.1111/jai.12161
|View full text |Cite
|
Sign up to set email alerts
|

Paternal effects on early life history traits in Northwest Atlantic cod, Gadus morhua

Abstract: SummaryIt is important to understand parental effects on early life history of fish as manifested, for example, in individual fitness of offspring. Immediately after fertilization, parental contributions (both genetic and non-genetic) to embryos will affect larval ontogeny, physiology, morphology and survival. In marine fish, rates of natural mortality are highest during early life and are negatively correlated with rates of growth and body size. In these early life stages (eggs, larvae, young juveniles) subtl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…For instance, paternal effects on ELH traits have been demonstrated for Atlantic salmon Salmo salar (Thorpe and Morgan, 1978;Houde et al, 2015), brown trout Salmo trutta (Vøllestad and Lillehammer, 2000), rainbow trout Oncorhynchus mykiss (Rinchard et al, 2003), chinook salmon Oncorhynchus tshawytscha (Pitcher and Neff, 2007), masu salmon Oncorhynchus masou (Yamamoto and Reinhardt, 2003), herring Clupea harengus (Panagiotaki and Geffen, 1992;Evans and Geffen, 1998), European sea bass Dicentrarchus labrax (Saillant et al, 2001), haddock Melanogrammus aeglefinus (Rideout et al, 2004), winter flounder Pseudopleuronectes americanus (Butts and Litvak, 2007a,b), Trinidadian guppy Poecilia reticulata (Reynolds and Gross, 1992), alpine whitefish Coregonus sp. (Wedekind et al, 2001) and Atlantic cod Gadus morhua (Butts et al, 2009;Kroll et al, 2013;Politis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, paternal effects on ELH traits have been demonstrated for Atlantic salmon Salmo salar (Thorpe and Morgan, 1978;Houde et al, 2015), brown trout Salmo trutta (Vøllestad and Lillehammer, 2000), rainbow trout Oncorhynchus mykiss (Rinchard et al, 2003), chinook salmon Oncorhynchus tshawytscha (Pitcher and Neff, 2007), masu salmon Oncorhynchus masou (Yamamoto and Reinhardt, 2003), herring Clupea harengus (Panagiotaki and Geffen, 1992;Evans and Geffen, 1998), European sea bass Dicentrarchus labrax (Saillant et al, 2001), haddock Melanogrammus aeglefinus (Rideout et al, 2004), winter flounder Pseudopleuronectes americanus (Butts and Litvak, 2007a,b), Trinidadian guppy Poecilia reticulata (Reynolds and Gross, 1992), alpine whitefish Coregonus sp. (Wedekind et al, 2001) and Atlantic cod Gadus morhua (Butts et al, 2009;Kroll et al, 2013;Politis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Parental experience could thus speed up offspring adaptive response to novel environmental conditions via a combination of epigenetics and sex-specific inheritance. While paternal-specific inheritance affects larval length in herring (Bang, Gronkjaer, Clemmesen, & Hoie, 2006) and hatching success in haddock (Rideout, Trippel, & Litvak, 2004) and Atlantic cod (Kroll, Peck, Butts, & Trippel, 2013), maternalspecific inheritance impacts egg and larval size across various fish species (Chambers & Leggett, 1996;Heath & Blouw, 1998;Marteinsdottir & Begg, 2002).…”
mentioning
confidence: 99%
“…Maternal effects on egg diameter have been studied in many fish species and are generally found significant, depending on diet, broodstock condition and timing in relation to the reproductive season (Laale, 1980; Kjørsvik et al , 1990; Morley et al , 1999). Similarly, paternal effects are important, impacting processes related to fertilization (Evans & Geffen, 1998; Kroll et al , 2013). In our study, wild-caught females were crossed with farmed males and we found a clear female effect that accounted for a large proportion of the models variance, e.g.…”
Section: Discussionmentioning
confidence: 99%